2018
DOI: 10.1016/j.freeradbiomed.2018.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of oxidative damage by targeting mitochondrial complex I in neonatal hypoxic-ischemic brain injury

Abstract: Rapid D→A conformation in response to reperfusion reactivates complex I. This is essential not only for metabolic recovery, but also contributes to excessive release of mitochondrial ROS and reperfusion injury. We propose that the initiation of reperfusion should be followed by pharmacologically-controlled gradual reactivation of complex I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 39 publications
(60 reference statements)
3
45
1
Order By: Relevance
“…The primary driver of such mitochondrial-derived reactive oxygen species (ROS) is an ischemic accumulation of the tricarboxylic acid (TCA) cycle metabolite succinate [ 3 , [11] , [12] , [13] ]. Data obtained from ischemic brain mitochondria have further suggested, that the flavin mononucleotide (FMN) site of complex I is responsible for the production of ROS via reverse electron transfer (RET), and that accumulation of succinate triggers release of FMN from mitochondrial complex I [ 2 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary driver of such mitochondrial-derived reactive oxygen species (ROS) is an ischemic accumulation of the tricarboxylic acid (TCA) cycle metabolite succinate [ 3 , [11] , [12] , [13] ]. Data obtained from ischemic brain mitochondria have further suggested, that the flavin mononucleotide (FMN) site of complex I is responsible for the production of ROS via reverse electron transfer (RET), and that accumulation of succinate triggers release of FMN from mitochondrial complex I [ 2 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current discoveries in the field of hepatic ischemia-reperfusion (I/R) point to mitochondrial-derived oxidative stress as key mechanism of tissue damage [1] , [2] , [3] . Optimization strategies for the treatment of ischemic organs may, therefore, depend on effective protection from mitochondrial injury.…”
Section: Introductionmentioning
confidence: 99%
“… 20 In another study, Kim et al. 21 reported that cerebral hypoxia–ischemia deactivated complex I. Curcumin can increase SOD levels and decrease MDA levels in hypoxic–ischemic brain injury in neonatal rats. 22 NSE levels are also an important factor in neurological function.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study showed a three to four-fold increase in oxidative protein carbonylation in the cortex, perirhinal cortex, and hippocampus of injured male rats with HIE, and increased glutathione peroxidase was found in female rats with HIE. 20 In another study, Kim et al 21 reported that cerebral hypoxia-ischemia deactivated complex I. Curcumin can increase SOD levels and decrease MDA levels in hypoxic-ischemic brain injury in neonatal rats. 22 NSE levels are also an important factor in neurological function.…”
Section: Discussionmentioning
confidence: 96%
“…Previous study has shown that secondary inflammation after HI has been shown to contributes to HI-induced brain injury (17). The toxic effects of inflammatory cytokines include both direct free radical release and indirect excitatory amino acid production (18).…”
Section: Discussionmentioning
confidence: 99%